2011
DOI: 10.1016/j.cub.2011.10.036
|View full text |Cite
|
Sign up to set email alerts
|

Visual Motion and the Perception of Surface Material

Abstract: Summary Many critical perceptual judgments, from telling whether fruit is ripe, to determining whether the ground is slippery, involve estimating the material properties of surfaces. Very little is known about how the brain recognizes materials, even though the problem is likely as important for survival as navigating or recognizing objects. Though previous research has focused nearly exclusively on the properties of static images [1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14,15,16], recent evidence suggests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
155
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(162 citation statements)
references
References 42 publications
7
155
0
Order By: Relevance
“…Therefore, it remains open whether the cortical regions respond to the phase congruency of complex spatial patterns per se or they respond to the phase information particularly related to gloss. To understand which of these alternative possibilities is more likely, it would be interesting to examine cortical responses using stimuli such as matte, textured ("sticky" reflection) objects (Doerschner et al, 2011;Hartung and Kersten, 2002) or matte objects with misaligned highlights in the future. Motoyoshi et al (2007) have recently found that the skewness of luminance histogram is positively correlated with the gloss perception in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it remains open whether the cortical regions respond to the phase congruency of complex spatial patterns per se or they respond to the phase information particularly related to gloss. To understand which of these alternative possibilities is more likely, it would be interesting to examine cortical responses using stimuli such as matte, textured ("sticky" reflection) objects (Doerschner et al, 2011;Hartung and Kersten, 2002) or matte objects with misaligned highlights in the future. Motoyoshi et al (2007) have recently found that the skewness of luminance histogram is positively correlated with the gloss perception in humans.…”
Section: Discussionmentioning
confidence: 99%
“…The rotating object continuously changed the position of its contour and specular highlights. It is also known that moving objects are perceived to be glossier than static ones, even when they are rendered with the same reflectance parameters (Doerschner et al, 2011;Sakano and Ando, 2010;Wendt et al, 2010). The mean luminance of each frame was set 20 cd/m 2 .…”
Section: Methodsmentioning
confidence: 94%
“…2C). Divergence and curl are representative optical field components that were typically used for describing fluid dynamics, and were thought to be important for other optical flow computations, including specular flow (Doerschner et al, 2011). Since these components are signed, the SD rather than the mean is a better index of how much curl or divergence is included in the movie.…”
Section: Purposementioning
confidence: 99%
“…For years, vision scientists have been investigating shape perception [Koenderink and Doorn, 1992] [Todd, 2004] [Doerschner et al, 2011]. Creating reliable noisy stimuli is a non-trivial task, especially when 3D stimuli are required.…”
Section: Introductionmentioning
confidence: 99%